Digital Revolution in Islamic Banking: Towards the Islamic Finance Era 5.0 - Masrina, Masrina; Patmawati, Sri; Fauziah, Nurul (IAIN Kudus, 2024)
This research examines the digital transformation in the Islamic banking industry towards the Islamic finance 5.0 era, with a focus on analyzing the impact of digitalization on operational efficiency, implementation challenges, and the development of effective governance models. Using a qualitative approach with an interpretive-constructivist paradigm, this study applies a systematic literature review with the PRISMA protocol to analyze primary sources from internationally reputable journals. The results show that digital transformation has resulted in a significant increase in operational efficiency, with a decrease in the Cost-to-Income Ratio of 12.5% and an increase in the accuracy of customer feasibility assessments by up to 78% through the implementation of big data analytics. The implementation of an artificial intelligence-based automation system in the sharia compliance screening process has reduced transaction processing time by up to 65%. The main challenges include the digital infrastructure gap, the complexity of sharia compliance in digital systems, and cybersecurity issues. The governance model developed integrates the Three Lines of Defense with the Digital Shariah Compliance Committee, resulting in an 83% reduction in the incidence of sharia non-compliance. The socio-economic impact can be seen from the increase in Islamic financial inclusion, with service penetration increasing by 156% in the last three years and the distribution of microfinance worth Rp 12.5 trillion to MSMEs. This research contributes to the development of a conceptual framework for digital transformation of Islamic banking that integrates aspects of technology, regulations, and sharia values, as well as provides practical recommendations for the sustainable development of digital Islamic banking.